ACADEMIC IMPAIRMENT, SOCIAL SUPPORT AND RESILIENT BEHAVIOR AMONG PHYSICALLY-CHALLENGED STUDENTS - Ehondor, Esohe G.; Daramola, Olajide; Uye, Emmanuel E (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2025)
This study investigated academic impairment and social support as predictors of resilient behavior among physically-challenged students. Cross-sectional research design was adopted while purposive sampling technique was used to select Lagos and Ekiti States, South-west Nigeria. Data were conveniently collected from 374 physically-challenged students using validated scales. Data collected were analyzed using multiple regression and t-test of independent samples to test four hypotheses at p 0.01 level of significance. The results indicated that academic impairment and significant others support independently predicted resilient behavior among physically-challenged students. Also, the result revealed that academic impairment and social support jointly predicted resilient behavior among study participants. The study concluded academic impairment and significant others' support are important predictors of resilient behavior among physically-challenged students.